ISO 27001 Information Security Management System: Effect of Firm Audits in Emerging Blockchain Technology - Tanadi, Yunita; Soeprajitno, Raden Roro Widya Ningtyas; Firmansah, Gery Lusiano; Karima, Tsanya El (Riset Akuntansi dan Keuangan Indonesia, 2021)
The emergence of Blockchain Technology is closely related to improving the ISO 27001 Information Security Management System for confidence in data and information security, preventing manipulation and various information risks that occur. This study examines the effect of the Audit Firm on companies that carry out ISO 27001 certification. This study uses 578 samples listed on the Indonesia Stock Exchange from 2013 – 2017. This study uses a quantitative method with OLS regression testing STATA 14. This study obtained the results that the Audit Firms have a significant influence at the 5% level on the company’s decision to improve the Information Security Management System as proxied by ISO 27001. This research has an empirical contribution to developing theory, participating in developing research related to ISO 27001 certification, and assessing the existence of an Audit Firm on the improvement of the Security Management System. Corporate information in the era of blockchain technology.